Psychophysiological patterns related to success in a special operation selection course (2019)
Actual theaters of operations require fast actions from special operations units with a high level of readiness and survival. Mission accomplishment depends on their psychological and physiological performance. The aim of the present study was to analyze: (1) the physical parameters related with success in a special operation selection course; and (2) the modifications of the psychological profile of recruits before and after a special operation selection course. Fifty-five male soldiers of the Spanish Army (25.1 ± 5.0 years, 1.8 ± 0.1 cm, 76.8 ± 7.9 kg, 24.4 ± 2.5 kg/m2) undertaking a 10-week special operation selection course performed a battery of physiological and psychological tests. Results showed how successful soldiers presented higher leg strength, anaerobic running performance, and cardiovascular response than non-successful soldiers. The psychological values of life engagement test, acceptance and action questionnaire, coping flexibility scale, and perceived stress scale did not present significant differences after the selection course. We can conclude that success in a special operation selection course was related to higher anaerobic and cardiovascular fitness. This special operation selection course did not modify the psychological profile of successful soldiers.